Integrating writing and speaking skills in EFL: a practice-oriented approach - Imamaliyeva, Gulnoza Ulug‘bekovna (The Lingua Spectrum, 2026)
This article presents an in-depth investigation of the integration of writing and speaking skills within the framework of integrated language instruction in English language teaching. The study examines the theoretical and methodological foundations of developing productive skills in a unified manner, emphasizing that the transition from oral formulation of ideas to their written consolidation promotes deeper cognitive processing of linguistic material. Such an approach harmonizes the spontaneity of spoken language with the analytical nature of written expression, thereby contributing to the formation of stable communicative competence. Empirical observations demonstrate that integrating these two modes of language production enhances learners’ cognitive engagement, strengthens their ability to conduct independent analysis, fosters creativity, and increases confidence in communicative interactions. The theoretical arguments are supported by practical examples drawn from real instructional contexts, illustrating the effectiveness of the methodology across diverse educational settings, including classroom activities and project-based learning. Special attention is given to student motivation, the creation of a supportive learning environment, and the development of intercultural competence as an essential component of contemporary language education. The article concludes that the integration of writing and speaking significantly improves learners’ practical command of English and plays a crucial role in preparing them for active participation in the global. communicative landscape.